Synthesis of imine bond containing insoluble polymeric ligand and its transition metal complexes, structural characterization and catalytic activity on esterification reaction. Issue 1 (1st January 2017) - Gönül, İlyas and Ay, Burak and Karaca, Serkan and Saribiyik, Oguz Yunus and Yildiz, Emel and Serin, Selahattin
Abstract: In this study, synthesis of insoluble polymeric ligand(L) and its transition metal complexes [Cu(L)Cl2 ]·2H2 O(1), [Co(L)Cl2 (H2 O)2 ](2) and [Ni(L)Cl2 (H2 O)2 ](3), having the azomethine groups, were synthesized by the condensation reactions of the diamines and dialdehydes. The structural properties were characterized by the analytical and spectroscopic methods using by elemental analysis, Fourier Transform Infrared, Thermo Gravimetric Analysis, Powder X-ray Diffraction, magnetic susceptibility and Inductively Coupled Plasma. The solubilities of the synthesized polymeric materials were also investigated and found as insoluble some organic and inorganic solvents. Additionally, their catalytic performance was carried out for the esterification reaction of acetic acid and butyl acetate. The highest conversion rate is 75.75% by using catalyst1 . The esterification of butanol gave butyl acetate with 100% selectivity.